REALISASI MANAJEMEN UNIT PELAYANAN BIMBINGAN DAN KONSELING (UPBK) PADA SEKOLAH MENENGAH PERTAMA (SMP) PERCONTOHAN DAN PENGEMBANG IMPLEMENTASI KURIKULUM 2013 DI KABUPATEN GOWA - Syaharuddin, Syaharuddin; Rezky, Amelia (COMPETITIVENESS, 2019)
The purpose of this research is to find out and analyze and trace: 1) The level of readiness of BK Teachers in the implementation of guidance and counseling services, 2) Implementation of guidance and counseling services, and 3) To find out the factors that affect the readiness of BK Teachers and the implementation of guidance and counseling services in order to realize the management of guidance and counseling in junior high school (SMP) pilot and developer of curriculum implementation 2013 in Gowa.The analysis used is the model "Cohen Kappa Index Analysis (AICK)" using research triangulation model in data collection, data reduction, data presentation, and conclusion drawing. The results of the study showed as follows: 1) In general, the development school implementation of curriculum 2013 in Gowa district has the readiness of BK Teachers in preparation for the implementation of guidance and counseling services, but still needs to be improved and developed according to school needs, especially in schools that lack and / or do not have bk teachers / counselors who are competent in carrying out the duties of guidance and counseling services. 2) In general, the development school implementation of curriculum 2013 in Gowa district has realized the target to achieve the implementation component of Guidance and Counseling Services, and 3) Factors that influence the implementation of guidance and counseling services can be seen that: a) In general the pilot school developer curriculum 2013 in Gowa district still needs a refresentative and adequate container to organize and implement all guidance and counseling services in the Guidance and Counseling Service Unit in schools. and b) In general, the pilot school of curriculum developer 2013 in Gowa district still needs guidance and counseling teachers (BK) who have the competency of graduates / alumni with educational background (S1) Guidance and Counseling or Bachelor of Psychology Education and Guidance. Keywords: Realization of Management, Guidance and Counseling Services.